Judicial Inactivism in Protecting Financial Consumers against Predatory Sale of Retail Structured Products: A Reflection from Retail Structured Notes Lawsuits in Taiwan - Chao-Hung, Christopher Chen (Columbia Journal of Asian Law, 2014)
This article analyzes 310 structured note lawsuits in Taiwan between 2000 and 2013 to examine courts’ attitude in dealing with claims of misselling retail structured notes. We find that courts were generally not favorable to retail investors. This provides a contrast with the financial regulator’s efforts to improve financial consumer protection since 2008. By examining plaintiffs’ key arguments and courts’ rulings, we find that it was difficult for investors to fulfill their burden of proof and courts were reluctant to award remedies when investors did sign on a contractual document confirming his knowledge on a few matters. While regulators are right to strengthen financial consumer protection, this article argues that Taiwan courts’ inactivism to protect retail investors could be justified. However, regulators should pick up from what courts have left to ensure that customers fully comprehend the consequences when they sign on contractual documents, to avoid banks classifying customers as active investors too easily, and to clarify banks’ duties toward a customer after a contract is signed. Regulators should also reconsider its regulatory structure to ensure foreign banks would not be able to issue securities to raise funds from local investors by way of a shadow banking system.